1998
DOI: 10.1079/phn19980030
|View full text |Cite
|
Sign up to set email alerts
|

Factors which influence ‘healthy’ eating patterns: results from the 1993 Health Education Authority health and lifestyle survey in England

Abstract: Objectives: This study explores the factors that influence eating patterns in a nationally representative sample of the English population. Design: Subjects were interviewed in 1993; questions covered basic demographic details, attitudes about nutrition, and they completed a short food frequency questionnaire that had previously been validated. Cluster analysis was used to summarize dietary intake into more or less healthy clusters. Settiq: A random sample ofthe English population. Subjects: A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 10 publications
4
28
0
1
Order By: Relevance
“…The observed association between family affluence and healthy habits is consistent with the findings of others that social status and income predict healthier food attitudes and a better diet (Margetts et al, 1998;Johansson et al, 1999). Amongst adolescents this relationship may be mediated in part by snacking behaviour, since a disadvantaged home life has been linked to less regular meal patterns and a higher consumption of sweet and fatty snacks in US adolescents (Siega-Riz et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed association between family affluence and healthy habits is consistent with the findings of others that social status and income predict healthier food attitudes and a better diet (Margetts et al, 1998;Johansson et al, 1999). Amongst adolescents this relationship may be mediated in part by snacking behaviour, since a disadvantaged home life has been linked to less regular meal patterns and a higher consumption of sweet and fatty snacks in US adolescents (Siega-Riz et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
“…Items on the checklist are relevant to dietary fibre intake through questions on fruit and vegetable consumption, and so a positive but weaker correlation was also predicted between dietary fibre and AFHC score. A positive correlation with family affluence was also predicted, as social class and income have both been associated with healthier eating practices (Margetts et al, 1998;Johansson et al, 1999). Furthermore the major role played by healthy eating in weight control (Nichter et al, 1995) meant that AFHC was hypothesised to be positively associated with dietary restraint.…”
Section: Introductionmentioning
confidence: 95%
“…Evidence from the NFS and NDNS, and from other studies in the United Kingdom (Margetts et al, 1998;Thompson et al, 1999) have shown that men are more likely than women to be lower consumers of fruit and vegetables and that there is also a strong age gradient in such consumption, with the 55 to 64 year age group eating twice as much fruit and vegetables as those under 25 years. As a result, we can expect the average fruit and vegetable consumption levels reported by our Seacroft respondents to be upwardly biased in relation to the NDNS average.…”
Section: Dietary Indicators Benchmarks and Pre-intervention Food-comentioning
confidence: 96%
“…Therefore the possibility of obtaining signi®cant results was larger for men than for women. In earlier studies in healthy subjects it has been shown that women are more likely to be more healthoriented than men (Margetts et al, 1997;Kearney et al, 1998;Roos et al, 1998). …”
Section: Men Womenmentioning
confidence: 98%
“…It has been postulated that healthy subjects with lower education and socioeconomic status would be less likely to consider diet as a health priority and be less willing to make dietary changes Margetts et al, 1998). However, it is not known whether these socioeconomic differences persist or change after an individual suffers from CHD.…”
Section: Introductionmentioning
confidence: 99%